Internet Parenting upon Indonesian Children - Dhahir, Darman Fauzan (Jurnal Pekommas, 2018)
Children living in the digital age are inseparable from the internet. It can lead them to success, and can also damage them at the same time. The role of parents is very important in this case because the parenting style influences the future of the children. This research was conducted due to the concern for the future of the nation. It aimed to determine internet parenting applied in Indonesia. It conducted with mix methods Bay using interview, observation and PSDQ survey techniques of data collection. After the data display and description, it resulted that the majority of parents in Indonesia apply to neglect parenting style. There was a lack of parents-children communication regarding the internet. The parenting style will allow the child to be trapped into the negative side of the internet. To avoid the increasing of the magnitude of the negative impact on children, the government is recommended to tighten internet filters, while increasing education to parents regarding internet care parenting, as well as children’s ICT literacy.